DETEKSI DINI KECURANGAN PADA PROGRAM KOPERASI MERAH PUTIH: ANALISIS KELEMBAGAAN DESA DAN IMPLEMENTASI MODEL SIPAK - Ridwan, Rizky; Riswandi, Dede; Setia Rachmanda, Yudi (JURNAL EKONOMI PERJUANGAN, 2025)
The Indonesian government plans to distribute IDR 550 trillion to villages nationwide through the Koperasi Merah Putih (Red and White Cooperative) program, raising serious concerns about institutional readiness and the potential for fraud. Cigalontang Subdistrict in Tasikmalaya Regency, which consists of 16 villages but has only three active cooperatives, exemplifies the limited cooperative infrastructure to manage public funds accountably. This study aims to explore internal control systems, fraud-triggering factors, and the effectiveness of early fraud detection mechanisms in the context of forming village cooperatives. Using a qualitative exploratory approach, data were collected through in-depth interviews, focus group discussions (FGDs), and document analysis. Findings reveal the absence of financial SOPs, transparent reporting, and internal auditing mechanisms in most village cooperatives. Factors such as economic pressure, poor financial literacy, and lack of reporting systems further increase the risk of fraud. As a solution, this study proposes the SIPAK Model (System, Integrity, Reporting, Accountability of Cooperatives) as a framework for developing a community-based early fraud detection system. This model is expected to serve as a policy reference and institutional strengthening strategy for more adaptive and transparent village cooperatives.